Dynamic mechanical analysis performance of pure 3D printed polylactic acid (PLA) and acrylonitrile butadiene styrene (ABS). (2022) - Arunprasath, K.; Vijayakumar, M.; Ramarao, M.; Arul, T.G.; Peniel Pauldoss, S.; Selwin, M.; Radhakrishnan, B.; Manikandan, V.
Abstract: Dynamic mechanical analysis (DMA) is a technique that is used to study the viscoelastic behaviour of polymeric materials. 3D printing is one of the well-known applications of additive manufacturing techniques which has wide areas of application. In that, Fusion Deposition modelling (FDM) has very fine outcomes with better printing qualities to execute good products. In this research work, the 3D printed samples of pure ABS and PLA were examined under dynamic mechanical analysis to study the various temperature heat, absorbing, storing, and dissipating behaviour of these samples. The results show, both ABS and PLA performed well under the heat flow categories. While comparing to conventional manufacturing technologies, these 3D printed DMA results are showing some excellent results. These polymeric samples may prepare as composites and used for various applications, for better outcomes and capabilities. Storage modulus, while taking the temperature values of ABS to 90 °C maximum and for PLA about 48 °C. This will happen, but this pure form of materials printed through FDM also has such a very good energy storing capacity. Considering the loss modulus energy dissipation in the form of heat started from 110 °C, this is one of the good signs on the fabricated technique and build quality of ABS. The continues decrease in the degree of crystallinity of the PLA and ABS increases the meshing strength noted in the damping factor.